Coping with pain among adults with chronic tic disorders - Małek, Agnieszka (Frontiers in Psychology, 2025)
IntroductionTic spectrum disorders—Gilles de la Tourette's syndrome (GTS) and Persistent (Chronic) Motor Tic Disorder (CMTD)—are neurodevelopmental conditions characterized by recurrent motor and/or vocal tics persisting for at least 1 year. While tics are the primary symptom, pain related to tics is an important yet often overlooked aspect of these disorders. Pain can result from the repetitive nature of tics, leading to muscle strain, joint stress, or even injury due to the forceful execution of movements. Additionally, pain resulting from rapid and repeated movements or vocalizations can contribute to chronic discomfort, significantly affecting daily functioning and quality of life. Despite its impact, tic-related pain is not always addressed in clinical practice, leaving individuals struggling to find effective management strategies. The aims of this study were to assess tic-related pain, pain coping strategies and beliefs, and to investigate whether individuals experiencing pain seek professional help and how effective they perceive such interventions to be.MethodsA total of 76 participants diagnosed with GTS and CMTD participated in the study. The following scales were used: Yale Global Tic Severity Scale (YGTSS), Visual Analog Scale (VAS), Short-Form McGill Pain Questionnaire-2 (SF-MPQ-2), Pain Coping Strategies Questionnaire (CSQ), Beliefs Questionnaire for Pain Control (BPCQ), and a survey containing demographic and health data and questions about pain management and its effectiveness.Results73.7% of participants reported tic-related pain; almost all of them declared pain located in more than one part of the body. Affective pain domain was the highest scored by both men and women. Coping self-statements was the most common coping strategy chosen by men, whereas catastrophizing was preferred by women. Respondents rated internal factors as the most important in pain management and external factors, particularly medical professionals, as the least important. This aligns with their experience, as fewer than one in five found professional interventions effective in relieving pain.ConclusionPain should be recognized as a common comorbid aspect of tic disorders and therefore both pharmacological and non-pharmacological interventions should include pain management. Chronic pain can significantly impair functioning in all areas of life and recommendations for the management of tic-related pain need to be developed.